Cytotoxic effects of an electromagnetic field on the meristematic root cells of lentils (Lens clunaris Medik.) - (:unkn) unknown (My University, 2010)
A comprehensive cytogenetic and cytochemical study was performed to elucidate the responses of mitotic activity, chromosomal behavior and intracellular Ca2+ deposition to extremely low-frequency (50-60 Hz) electromagnetic fields (EMFs), generated by direct current (DC) and alternative current (AC) on lentil root tips. Germinated lentil seeds were exposed to EMFs by different doses of AC and DC for 3, 6 and 12 h. It was revealed that mitotic index decreased according to long EMF exposure period and high dose, and it decreased to zero at 1000 G. The mitotic abnormalities were observed in both treated roots, such as chromosome bridges, stickiness, lagging chromosomes, micronuclei and binucleated cells, confirming their cytotoxic effects. Degradation of cytoplasm and deformation of plasma membrane were also noted. Although AC and DC exposures exhibited similar percentages of total abnormalities, some mitotic abnormalities were special to one potential. In order to identify alterations of intracellular Ca2+ deposition, the lentil root sections were visualized cytochemically, and it was obviously observed that EMF exposed root tips were densely stained compared to control, depending on time and dose. As a conclusion, EMF exposure increased chromosomal abnormalities and intracellular Ca2+ deposition, accompanied by deformation of cytoplasm and plasma membrane, however, reduced the mitotic division frequency. © by PSP.
Keywords: Alternative current; Chromosomal behavior; Direct current; Intracellular Ca2+ deposition; Mitotic index